Child Abandonment And Its Implications For Educational Development In Nigeria - Onyido, Josephine Azuka; Akpan, Bokime Gabriel (Archives of Business Research, 2018)
This is a position paper that examined child abandonment and its implications for educational development in Nigeria. Child abandonment is a common social phenomenon in Nigeria and the rate at which the act is been committed calls for serious action by all in order to minimize the impact of this ugly menace on our society. The paper therefore identified the causes and effects of child abandonment which ranges from family conflicts, barbaric cultural practices, poverty and homelessness, and intra/inters ethnic conflicts among others. The paper emphasis that when a child is abandoned, the child is faced with physical, behavioural, psychological consequences and the society faces the bulk of these consequences. It was recommended amongst others that government should ensure strict monitoring of the child rights acts in all the states, conflicts in the family should be settled amicably, youths and intending parents should be properly counselled on the roles of parenting. It was concluded that education is a vital tool which should be used as an instrument to minimize child abandonment in the society.